Sepsis, oxidative stress, and hypoxia: Are there clues to better treatment?. (September 2015) - Bar-Or, David; Carrick, Matthew M.; Mains, Charles W.; Rael, Leonard T.; Slone, Denetta; Brody, Edward N.
<x content-type="archive" xml:space="preserve">Abstract</x> Sepsis is a clinical syndrome characterized by systemic inflammation, usually in response to infection. The signs and symptoms are very similar to Systemic Inflammatory Response Syndrome (SIRS), which typically occur consequent to trauma and auto-immune diseases. Common treatments of sepsis include administration of antibiotics and oxygen. Oxygen is administered due to ischemia in tissues, which results in the production of free radicals. Poor utilization of oxygen by the mitochondrial electron transport chain can increase oxidative stress during ischemia and exacerbate the severity and outcome in septic patients. This course of treatment virtually mimics the conditions seen in ischemia–reperfusion disorders. Therefore, this review proposes that the mechanism of free radical production seen in sepsis and SIRS is identical to the oxidative stress seen in ischemia–reperfusion injury. Specifically, this is due to a biochemical mechanism within the mitochondria where the oxidation of succinate to fumarate by succinate dehydrogenase (complex II) is reversed in sepsis (hypoxia), leading to succinate accumulation. Oxygen administration (equivalent to reperfusion) rapidly oxidizes the accumulated succinate, leading to the generation of large amounts of superoxide radical and other free radical species. Organ damage possibly leading to multi-organ failure could result from this oxidative burst seen in sepsis and SIRS. Accordingly, we postulate that temporal administration with anti-oxidants targeting the mitochondria and/or succinate dehydrogenase inhibitors could be beneficial in sepsis and SIRS patients.